Diuretic therapy choice in the treatment of arterial hypertension and heart failure - M. P. Savenkov; A. V. Kirichenko; S. N. Ivanov; M. V. Borshchevskaya; I. N. Okuneva (Кардиоваскулярная терапия и профилактика, 2009)
Aim. То evaluate the diagnostic potential of the combination of 24-hour blood pressure and diuresis monitoring (CBPDM), to study the associations between diuresis and blood pressure (BP), to compare diuretic and antihypertensive activity of thiazide diuretics (tD) — hydrochlorothiazide (Hct) and loop diuretics (ID) such as furosem-ide and torasemide.Material and methods. In 110 patients with arterial hypertension (AH) and congestive heart failure (HF), CBPDM was performed with 1-, 3-hour and functional intervals (morning, day, evening, and night), combined with a diuretic taken once a day: Hct, furosemide and torasemide (100, 20 and 5 mg/day, respectively).Results. CBPDM demonstrated a strong correlation (r=0,5—0,75) between BP and diuresis in the patients examined. CBPDM with functional intervals was recommended for clinical practice use. CBPDM potential for circadian fluid and electrolyte metabolism and BP assessment, diuretic choice and effectiveness control was demonstrated. Torasemide benefits are related to its earlier, longer and more effective diuretic activity, as well as with lower risk of arterial hypotension.Conclusion. CBPDM is an important method for studying renal mechanisms of HF and AH, diagnosing fluid metabolism disturbances, choosing diuretic therapy and controlling its effectiveness. Diuretic therapy choice should be based on fluid balance assessment, taking into consideration the benefits of a ID torasemide.